Ecophysiological responses of two closely related Magnoliaceae genera to seasonal changes in subtropical China. (18th February 2017) - Liu, Hui; Zhu, Liwei; Xu, Qiuyuan; Lundgren, Marjorie R; Yang, Keming; Zhao, Ping; Ye, Qing
Abstract: Aims: Plants use a variety of hydraulic strategies to adapt to seasonal drought that differ by species and environmental conditions. The early-diverging Magnoliaceae family includes two closely related genera with contrasting leaf habits, Yulania (deciduous) and Michelia (evergreen), which naturally inhabit temperate and tropical regions, respectively. Here, we evaluate the hydraulic strategy of species from both genera that have been ex situ conserved in a subtropical region to determine how they respond to the novel cool–dry season climatic pattern. Methods: We measured ecophysiological traits in five Michelia and five Yulania species conserved in the South China Botanical Garden in both wet and dry season conditions and monitored the whole-year sap flow for four of these species. Important Findings: We found that Magnoliaceae species that have been ex situ conserved in a subtropical climate did not suffer from excessive water stress due to the mild drought conditions of the dry season and the ecophysiological adjustments the species made to avoid this stress, which differed by leaf habit. Specifically, deciduous species completely shed their leaves during the dry season, while evergreen species decreased their turgor loss points, dry mass based photosynthetic rates, stomatal conductance and specific leaf areas (SLAs) compared to wet season measurements. In comparing the two distinct leaf habits during the wet season, the leathery-leaved evergreen species had higher leaf hydraulic conductance and leaf to sapwood area ratios than the papery-leaved deciduous species, while the deciduous species had greater hydraulic conductivity calculated on both a stem and leaf area basis, dry mass based photosynthetic rates, leaf nutrients, SLAs and stomatal sizes than the evergreen species. Interestingly, species from both genera maintained similar sap flow in the wet season. Both photosynthetically active radiation and vapour pressure deficit affected the diurnal patterns of sap flow in the wet season, while only vapour pressure deficit played a dominant role in the dry season. This study reveals contrasting hydraulic strategies in Yulania and Michelia species under subtropical seasonal conditions, and suggests that these ecophysiological adjustments might be affected more by leaf habit than seasonality, thus reflecting the divergent evolution of the two closely related genera. Furthermore, we show that Magnoliaceae species that are ex situ conserved in a subtropical climate are hydraulically sound, a finding that will inform future conservation efforts of this ancient family under the threat of climatic change.